The Relationship Between Musculoskeletal Disorders, Anxiety and Body Awareness in Elite Athletes - Atakan Gürgan; Beyzanur Dikmen Hoşbaş; Berna Karamancıoğlu; Deniz Demirci (Türk Spor ve Egzersiz Dergisi)
Objective: The aim of this study was to determine the most common musculoskeletal disorders in athletes and to investigate the relationship between musculoskeletal complaints and sport-related anxiety and body awareness. Methods: This study, which was designed using the relational screening method as a quantitative research, was conducted using the online survey method (via Google Forms). The study included 80 athletes aged 18-35 years, who were actively involved in elite level sport. The Nordic Musculoskeletal Questionnaire was used to assess musculoskeletal disorders, the Sports Anxiety Scale-2 (SAS-2) to assess anxiety, and the Body Awareness Questionnaire (BAQ) to assess body awareness. Results: There was a significant difference in somatic anxiety levels between the athletes who experienced musculoskeletal pain and those who did not (p<0.05). The somatic anxiety levels of athletes with musculoskeletal disorders were found to be higher than those without musculoskeletal disorders. A weak correlation at a high level of significance was found between athletes' somatic anxiety levels and the number of areas of complaint reported in the last 12 months and athletes' somatic anxiety levels (p<0.01). With the body awareness status of the athletes; while a positive significant weak level relationship was found with somatic anxiety level (p<0.05), a negative negative relationship was found with concentration disorganisation at a high level of significance ( p<0.05). Conclusion: It was observed that athletes with musculoskeletal disorders had higher levels of somatic anxiety and that the number of regions in which the athlete experienced complaints was related to the level of somatic anxiety; there was no relationship between body awareness levels and musculoskeletal complaints. A multidisciplinary study with a psychological perspective is important for the clinical care and support of elite athletes in different sports.